The Diagnosis and Treatment Status of Common Diseases in Pet Dogs - Zhang, Ruihan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
With the improvement of people’s living standards, more and more people need the companionship of pets, and pet dogs are the largest proportion of all kinds of pets, and the number of people entering the human family is also constantly surging, becoming a member of the human family. However, pet dogs are not always healthy, and a variety of common diseases endangering the health of pets will also break out in pet dogs, which requires strengthening the prevention and treatment of common diseases of pet dogs, reducing the pain caused by pet diseases, reducing the mental pain of pet owners, and reducing the economic burden of families. Breeding personnel must deeply understand the importance of pet dog epidemic prevention and control, in addition to seriously do a good job in the daily breeding of feeding, cleaning, disinfection, but also should pay close attention to the external performance of the dog, in order to strictly grasp the prevention and control of pet dog epidemic.